2008
DOI: 10.1189/jlb.1107783
|View full text |Cite
|
Sign up to set email alerts
|

C-Jun NH2 terminal kinase (JNK) is an essential mediator of Toll-like receptor 2-induced corneal inflammation

Abstract: TLRs play an important role in the host inflammatory response to bacteria and bacterial products by activating a cascade of intracellular events leading to production of proinflammatory and chemotactic cytokines. To determine the role of MAPKs in TLR-induced corneal inflammation, we stimulated human corneal epithelial (HCE) cells with TLR2 ligands, tripalmitoyl-S-glyceroCys-(Lys)4 (Pam3Cys) or inactivated Staphylococcus aureus, and examined the time course of expression of MAPKs and the effect of MAPK inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 36 publications
6
49
2
Order By: Relevance
“…Indeed, JNK Ϫ/Ϫ mice had decreased responses to S. aureus-stimulated inflammation. Our results differ somewhat from those of Adhikary et al (40) in that both JNK and ERK were required for the expression of TGF␤. These differences are possibly due to cell type specificity in responses.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Indeed, JNK Ϫ/Ϫ mice had decreased responses to S. aureus-stimulated inflammation. Our results differ somewhat from those of Adhikary et al (40) in that both JNK and ERK were required for the expression of TGF␤. These differences are possibly due to cell type specificity in responses.…”
Section: Discussioncontrasting
confidence: 57%
“…These include activation of NFB, JNK, ERK, and p38 (63). Adhikary et al (40) studied TLR2-specific signaling pathways and showed that Pam3Cys stimulation of corneal epithelial cells resulted in phosphorylation of JNK, ERK, and p38 but that only blockade of JNK had an inhibitory effect on activation of NFB. Indeed, JNK Ϫ/Ϫ mice had decreased responses to S. aureus-stimulated inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After Passage 1, antibiotics were omitted from the culture medium, and cells were harvested with 0.25% trypsin and transferred to a 50-cm 2 flask. The medium was changed every 4 days, and cells from passages 2-5 were used for experiments when cells were 70% confluent (21).…”
Section: Methodsmentioning
confidence: 99%
“…As mouse primary corneal epithelial cells are difficult to culture and cell lines are not available, we examined the effect of IFN-␥ on MD-2 mRNA and protein expression in primary human corneal epithelial (HCE) cells in an SV40-transfected HCE cell line (HCEC) (9,21,26) and in a telomerase immortalized HCE cell line (HCET) (20).…”
Section: Ifn-␥ Up-regulates Expression Of Md-2 But Not Tlr4 Tlr2 Omentioning
confidence: 99%